2018
DOI: 10.1111/anae.14379
|View full text |Cite
|
Sign up to set email alerts
|

Premedication in children: does taste matter?

Abstract: Sedative premedication is commonly prescribed for anxious, non-compliant children, those who have been distressed previously, and those with learning disabilities or behavioural issues. In addition, the type of procedure and its likely duration may influence the choice of sedative. The aims of premedication in children include: allaying their anxiety; allowing easy separation from their parent or carer; facilitation of a smooth anaesthetic induction; and a reduction in postoperative psychological problems. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…This contrasts with our findings that both drugs had a similar rejection rate 8,14 . Flavored preparations of the drugs might be used to increase compliance for the oral premedications 31 …”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with our findings that both drugs had a similar rejection rate 8,14 . Flavored preparations of the drugs might be used to increase compliance for the oral premedications 31 …”
Section: Discussioncontrasting
confidence: 99%
“…Flavored preparation of midazolam—such as the midazolam hydrochloride syrup used in the United Kingdom 8 and chocolate-flavored midazolam tablet in Australia—helps increase compliance with its oral premedication. 13 Unfortunately, only the IV midazolam formulation is currently available in China.…”
Section: Discussionmentioning
confidence: 99%
“…5–7 In the United Kingdom, midazolam hydrochloride syrup is dispensed at a 2 mg/mL concentration. 8 This oral formula is not available in China, and the midazolam intravenous (IV) formulation—a bitter-tasting drug—is used for oral administration in our institution. Because children are naturally fond of sugar, and because syrup is commercially available in China, we aimed to assess whether syrup added as a flavoring to oral IV midazolam could improve its tolerability in clinical administration.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, the bitter taste of this medication often results in poor tolerance in young children and adolescents. 7 Therefore, attempts to mask this medication have been made, such as the formulation of oral midazolam syrups, albeit to no avail. 8 However, a clinical trial involving paediatric patients and their carers 8 , have demonstrated the e cacy of the novel chocolate delivery platform to mask the bitter taste of midazolam.…”
Section: Introductionmentioning
confidence: 99%